Preparation of esophageal fistula for maximum recovery of ingested herbage - Carvalho, Elusio G.; Euclides, Valéria P. B. (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of determining the recovery of herbage, ten steers averaging 220 kg of liveweight were fistulated at the esophagus. The only difference from the usual surgical procedure was that a largar incision was made at the esophagus, to make a range in fistula diameters varying from 5 to 8 cm. ln the first six months after surgery, the fistula diameters lncreased in size, varying from 1 to 4 cm. The major post-operative problem was the excessive leakage from the fistula in six animals. In four of them the leakage was controlled by adjusting the plug sizes. However, In the two other steers this adjustment did not work, and those fistulas were finally reduced by suturing. The percentage recovery of extrusa was checked with brachiaria (Brachiaria decumbens), 2-week regrowth, and elephant grass (Pennisetum purpureum), mature, offered to the animals during ten days each. The percentage of recovered herbage was obtained by dividing the organic matter weight of esophageal extrusa by organic matter weight of ingested forage. Recovory rate was lower (P < 0.06) for elephant grase than for brachiaria. The organic matter recovory was positively correlated (r² = 0.96 and P < 0.01) with the fistula diameter. A fistula of more than 8 cm of diameter was necessary for obtaining consistent high recoveries.
Keywords: steer; surgical procedure; post-operative care; leakage.